Risk assessment and nutritional prognosis of clinical outcome in critically ill patients - Souza, Janderson Pinheiro de; Vermeulen-Serpa, Karine Marques; Lopes, Márcia Marília Gomes Dantas; Vale, Sancha Helena de Lima; Leite-Lais, Lucia (ABCS Health Sciences, 2023)
Introduction: Nutrition assessment of critically ill patients is challenging but it should be part of the clinical nutrition routine in the hospital setting. Objective: To assess the nutritional risk and prognosis of patients admitted to the intensive care unit (ICU) of a University Hospital in Natal, Brazil. Methods: Cross-sectional study developed with adult and elderly patients between February 2017 and February 2020. The nutritional risk was detected by the modified Nutrition Risk in Critically Ill score (mNUTRIC-score). The nutritional prognosis was assessed using the phase angle (PA), calculated from the resistance and reactance values provided by bioimpedance. Mann-Whitney test was used to verify the association of mNUTRIC-score and PA with the outcome (hospital discharge or death). Spearman’s correlation coefficient was used to verify the correlation between mNUTRIC-score and PA. Results: A total of 55 patients were included in this study. The average value of the NUTRIC score and PA was 3.13 ± 2.35 and 4.19 ± 1.21, respectively. Most patients had low nutritional risk. Among them, 81.8% were discharged and 18.2% died. Both mNUTRIC-score (p≤0.0001) and PA (p=0.04) were associated with the clinical outcome. These two parameters were negatively correlated (r=-0.3804; p=0.0059). Conclusion: Most of the patients had a low nutritional risk determined by the mNUTRIC-score. Those with high nutritional risk had a worse outcome (death). A negative correlation was observed between the mNUTRIC score and the PA, showing that the higher the nutritional risk, the worse prognosis was found in critically ill patients.